2007
DOI: 10.1007/s10608-006-9118-6
|View full text |Cite
|
Sign up to set email alerts
|

Neurobehavioral Therapies in the 21st Century: Summary of an Emerging Field and an Extended Example of Cognitive Control Training for Depression

Abstract: The promise of a new generation of therapies targeted to address neurobiological mechanisms thought to underlie psychological disorders, particularly depression, using cognitive and behavioral techniques is discussed. Relationships between such neurobehaviorally focused therapies and other psychological and rehabilitative interventions are also discussed. Their potential utility as adjuncts to conventional treatment, and the importance of multi-method assessment in their evaluation are emphasized. Finally, ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
424
2
10

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 398 publications
(451 citation statements)
references
References 140 publications
(129 reference statements)
15
424
2
10
Order By: Relevance
“…In a subsample of six individuals, these authors also used fMRI assessment before and after the training. The results showed that after the intervention, depressed participants displayed decreased disruptions in both amygdala activity on an emotion task and in DLPFC activity on a cognitive task on which they were not trained (Siegle, Ghinassi & Thase, 2007). This is a first study showing that a combination of regular approaches and cognitive control training may have extra value in the treatment of depression.…”
Section: Cognitive Controlmentioning
confidence: 83%
“…In a subsample of six individuals, these authors also used fMRI assessment before and after the training. The results showed that after the intervention, depressed participants displayed decreased disruptions in both amygdala activity on an emotion task and in DLPFC activity on a cognitive task on which they were not trained (Siegle, Ghinassi & Thase, 2007). This is a first study showing that a combination of regular approaches and cognitive control training may have extra value in the treatment of depression.…”
Section: Cognitive Controlmentioning
confidence: 83%
“…Importantly, longitudinal studies and cognitive bias modification (CBM) research (i.e., experimental manipulation of processing biases) have shown that cognitive control deficits (Siegle, Ghinassi, & Thase, 2007;Zetsche & Joormann, 2011), biases in attention (Beevers & Carver, 2003;, interpretation (Blackwell & Holmes, 2010;Holmes, Lang, & Shah, 2009;Rude, Valdez, Odom, & Ebrahimi, 2003;Rude, Wenzlaff, Gibbs, Vane, & Whitney, 2002), and memory processes (Johnson, Joormann, & Gotlib, 2007;Raes, Williams, & Hermans, 2009;Sumner, Griffith, & Mineka, 2010) can predict and contribute to the onset and maintenance of depressive symptoms. Moreover, these distorted cognitive processes can be found in at-risk (Dearing & Gotlib, 2009;Joormann, Talbot, & Gotlib, 2007;Kujawa et al, 2011;Taylor & Ingram, 1999) and remitted (Fritzsche et al, 2010;Gilboa & Gotlib, 1997;Hedlund & Rude, 1995;, 2010 depressed samples.…”
Section: Cognitive Biases and Vulnerability For Depressionmentioning
confidence: 99%
“…Given the maintaining role of information processing biases, it is important to consider the potential value of targeted cognitive training that can either train neural structures known to be impaired in depression (Siegle et al, 2007) or modify emotion specific biases in attention (Baert, De Raedt, Schacht, & Koster, 2010;, interpretation (Blackwell & Holmes, 2010;Holmes, Lang, & Shah, 2009;Lang, Blackwell, Harmer, Davison, & Holmes, 2011) or memory (Joormann, Hertel, LeMoult, & Gotlib, 2009;Raes et al, 2009). In general, cognitive bias modification (CBM) methodologies target specific cognitive processes by exposing participants to experimentally established contingencies during a task designed to encourage the acquisition or attenuation of an information processing bias ).…”
Section: Modification Of Cognitive Biasesmentioning
confidence: 99%
“…In recent years, important progress has been made in this area, using modified working memory training tasks such as the adaptive Paced Auditory Serial Addition Task (PASAT; e.g., Siegle, Ghinassi, & Thase, 2007) to train cognitive 5 control. During the adaptive PASAT, participants are presented with a stream of auditory presented digits and are instructed to indicate the sum of the last two digits, which relies on continuously updating working memory.…”
mentioning
confidence: 99%
“…Depending on the accuracy of the responses, the inter stimulus interval (ISI) would decrease or increase, modifying task difficulty. Siegle et al (2007) demonstrated the added value of combining cognitive control training (CCT) with treatment as usual (TAU), which led to a greater reduction in rumination and depressive symptomatology compared to a TAU control group. These findings have recently been replicated and extended, showing a reduced need for outpatient services one year following the combined intervention (Siegle et al, 2014).…”
mentioning
confidence: 99%